Study on the Dynamics of 3HUS+S Parallel Bionic Hip Joint Simulator - Zhang Huizhen; Cheng Gang; Shan Xianlei (Jixie chuandong)
In order to analyze the dynamics characteristic of the hip joint simulator which taking the 3HUS+ S spatial parallel mechanism as the core module,starting from the kinematics of parallel mechanism,the relationship between the velocity,acceleration of moving platform and the linear module slider and active branched- chains are established. By the forces and torques of the centroid of the moving platform,active branched- chains and linear module,the dynamics model is established based on the principle of virtual power. The driving torques and powers of the linear module are obtained by simulating on the dynamics model,a reference for the simulator in the analysis of dynamics characteristics and research of control strategy is provided.